Investigation of the Effectiveness of Phonological Working Memory Intervention on Decreasing of Severity Of Stuttering in Preschool Children: A Single-Subject Research - Marziyeh Amini; Bijan Shafiei; Ahmad Abedi (Vesnu Publications, 2015)
Introduction: Working memory is one of the components of speech production and its deficiency can cause speech and language disorders. Several studies have suggested that children who stutter compared to normal children show some deficiencies in working memory. The aim of the present study was to investigation of the effectiveness of phonological working memory intervention on decreasing of severity of stuttering in preschool children. Materials and Methods: This study with single subject design targeted four children (5-6 years) who stutter. These children participated in a non-word repetition intervention, was scheduled in 18 sessions, over a total of six weeks and with a single subject research design (AB model). In order to analyze the data of the study, visual analysis of charts and quantitative analysis based on Cohen's d effect Size were used. Results: Data analysis showed all participants recorded a statistically significant change, as a decline in percentage of syllables stuttered, following the intervention. Conclusion: The results from this study suggest that an intervention of phonological working memory eventuated in decreases of severity of stuttering in children participated in this study; conseqently, these results provide the preliminary evidence that supports the usage of a psycholinguistic approach for treatment the stuttering in children who stutter.